An Assessment of Lower Respiratory Tract Infections in Paediatrics–A Seasonal Study - Rajan, Nisha; Sankar, Binai Kochunni; Mruthyunjaya, Prasad Sivanna (Indian Journal of Pharmacy Practice)
Introduction: Paediatrics are a group of population vulnerable to many infections. Among these infections, the burden of RTIs are growing faster day by day because of the poor lifestyle, polluted environment and even inadequate care given to them when they are born. LRTIs have been affecting the quality of life of a number of children which can even turn fatal. Early detection, treatment and prevention can improve the later life of a child. At the same use of therapeutic agents in such infections need to be studied. Antibacterials have been playing a very important role since decades. Hence judicious use of such agents are necessary to make sure that, this special age group would not develop any resistance in future. Objective: To study the incidence of LRTI and use of antibacterials in paediatrics. Methodology: This is a prospective observational study carried out over a period of three months among In-patients and Out-patients in the department of Paediatrics. The patient’s bystanders were briefed about the study and consent was obtained prior to their enrollment. All the patients visiting the OP as well as admitted to the hospital being treated with a single or multiple antibacterial agent were reviewed on a daily basis by the clinical pharmacist. All the documented data were evaluated by applying appropriate statistical methods. Result: A total of 80 patients were enrolled in which 92.5% were found be in the age range of 0 to 5 years. Males (57.5%) were found to be affected more than females. The number of patients in IP was more, 56.25%. In the month of February, 86% of the patients were seen visiting OP whereas in December 67% were admitted to the Hospital. It was found that 98% of the cases were caused by bacteria. Most of them, (80%) received antibacterial therapy. Amoxicillin–clavulanic acid combination was most (37.5%) commonly used and injectable were preferred. Supportive therapy was also given, and maximum patients, 27.70% were on nebulization. Conclusion: This study concludes that children below the age of 5 years are greatly vulnerable to LRTI. The number of cases increased as the temperature decreased. Combination of antibacterials are preferred in the present scenario which show the development of resistance. Hence, rational prescribing of antibacterials is necessary. Moreover, culture tests are to be performed prior to the initiation of therapy so that unwanted use can be controlled. The Paediatricians should strictly stick to the guidelines so that quality of life of children can be improved.
Keywords: Antibacterials; Paediatrics; LRTI; Supportive therapy; Culture tests; Temperature fluctuations